Patients’ attitudes to discontinuing not-indicated long-term antidepressant use: barriers and facilitators - Eveleigh, Rhona (Ther Adv Psychopharmacol, 2019)
BACKGROUND: Long-term antidepressant use has increased exponentially, though this is not always according to guidelines. Our previous randomized controlled trial (RCT) showed that participants using antidepressants long term without a proper indication were apprehensive to stop: only half were willing to attempt to discontinue their antidepressant use. The objective of this study was to explore participants’ barriers and facilitators for stopping long-term antidepressant use without a current proper indication. METHODS: Semistructured interviews with participants from the intervention group of our RCT, a cluster-RCT in general practice in the Netherlands. The latter study was a stop trial with patients on long-term antidepressant use without a current indication (no psychiatric diagnosis). Participants of the intervention group of the RCT had been provided with advice to stop antidepressants. Participants of the current interview study were purposively sampled (from the intervention group of the RCT) to ensure diversity in age, sex, and intention to discontinue the antidepressant. Analysis was performed as an iterative process, based on the constant comparative method. Data collection proceeded until saturation was reached. RESULTS: A total of 16 participants were interviewed. Fear (of recurrence, relapse, or to disturb the equilibrium) was the most important barrier; prior attempts fueled these anticipations. Also prominent as a barrier was the notion that antidepressants are necessary to counter a deficiency of serotonin. Facilitators were information on duration of usage given at the time of first prescription and confidence in a successful attempt. We found many participants struggling between barriers and facilitators to discontinue and participants not discontinuing while experiencing no barriers (ambivalence). CONCLUSION: Fear is an important motive for patients considering discontinuation of antidepressants. Serotonin deficiency as explanation for antidepressant effectiveness promotes life-long use and hinders discontinuation of antidepressant treatment. The prospect of discontinuation at first prescription can facilitate a future discontinuation attempt. General practitioners should be aware of their patients’ fears, expectations, and attributions toward antidepressant use/discontinuation, and of new developments in taper methods.